2018
DOI: 10.1089/ars.2017.7302
|View full text |Cite
|
Sign up to set email alerts
|

The p53 Family in Brain Disease

Abstract: Understanding the molecular mechanism(s) underlying the function of the p53 family could improve our general knowledge of the pathogenesis of brain disorders and potentially pave the road for new therapeutic intervention. Antioxid. Redox Signal. 29, 1-14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 166 publications
0
13
0
Order By: Relevance
“…Future investigation might add a further step in the comprehension of such transcriptionl regulation; it might occur that specific repressors take part and help coordinate the repression of the downstream miR sequence upon ELF exposure. P73 and ΔNp73 for instance share the same regulatory sequences with p53 on many different gene promoters likely including miR-34 [76] and are specifically involved in gene transcription in brain where they control physiological and pathological pathways [77,78]. ΔNp73α in particular works as an antagonist of p53/p73 functions in growth suppression and/or apoptosis and might be involved in miR-34 inhibition in response to ELF.…”
Section: Discussionmentioning
confidence: 99%
“…Future investigation might add a further step in the comprehension of such transcriptionl regulation; it might occur that specific repressors take part and help coordinate the repression of the downstream miR sequence upon ELF exposure. P73 and ΔNp73 for instance share the same regulatory sequences with p53 on many different gene promoters likely including miR-34 [76] and are specifically involved in gene transcription in brain where they control physiological and pathological pathways [77,78]. ΔNp73α in particular works as an antagonist of p53/p73 functions in growth suppression and/or apoptosis and might be involved in miR-34 inhibition in response to ELF.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that maternal folic acid deficient increased apoptosis of neural cells both in hippocampus and cortex in rat offspring. Apoptosis is executed by some members of evolutionarily conserved members of the Bcl‐2 family, caspase family, and TP53 family (Matusica et al, 2016; Agostini et al, 2018). TP53 activates several apoptotic genes (Tembe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Together with the frequent p53 mutations in cancer [ 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ], this signalling leads to associate their function to oncosuppression [ 123 , 124 , 125 , 126 ]. There is, however, strong in vivo and in vitro evidence that the family is also implicated in the regulation of the CNS functions [ 127 , 128 , 129 , 130 , 131 ]. Mechanistically, the p53-family proteins control NSCs survival, self-renewal and terminal differentiation via a complex transcriptional regulatory network by binding to specific DNA sequences to regulate the expression of coding- and non-coding genes.…”
Section: Transcriptional Regulation Of Adult Neurogenesismentioning
confidence: 99%